STRENGTHENING THE QUALITY OF HUMAN RESOURCES AND ECONOMIC ACCESS OF LOCAL COMMUNITIES IN IMPROVING SOCIAL INTEGRATION IN THE CAPITAL CITY OF NUSANTARA - K.P.Suharyono S.Hadiningrat; Dewanto Soedarno; Verry Albert Jekson Mardame Silalahi (JIPOWER : Journal of Intellectual Power, 2024)
The relocation of the Indonesian Capital City from Jakarta to the Capital City Of Nusantara in East Kalimantan is a strategic step that is expected to bring major changes to the community, including the local community, both in terms of social, economic and cultural aspects. This research aims to identify factors that support the strengthening of the quality of human resources (HR) and economic access and evaluate their impact on social integration in the Nusantara Capital City. The methodology used is descriptive qualitative with a literature study approach, which allows in-depth analysis of relevant literature to build a conceptual framework and effective HR development and economic access strategies. The results show that strengthening the quality of human resources through increased access to education and skills training is essential to ensure local communities are able to adapt to the social and economic changes taking place. On the other hand, improving economic access that includes easy access to capital, market access, and adequate infrastructure is needed to create equitable economic opportunities for all levels of society. The results of this study confirm that the success of the relocation of the Capital City does not only depend on physical development, but simultaneously the quality of human resources of local communities and migrants must be built in order to realize harmonious and inclusive social integration. For this reason, affirmative policies are needed for vulnerable groups through strengthening access to the education sector and sustainable training, increasing economic access through financial inclusion, and social integration strategies that strengthen community cohesion. Thus, the Nusantara can become a model of inclusive sustainable development, which supports the welfare of local communities amidst major changes. In addition, the central government, Nusantara Capital City (IKN) Authority and other local governments to collaborate in supporting the successful development of the Nusantara Capital City.